PENURUNAN BOD dan TSS PADA LIMBAH INDUSTRI SAUS SECARA ELEKTROKOAGULASI MENGGUNAKAN ELEKTRODA Fe, Cu dan STAINLESS - Yuliani, Ika; alimuddin, Alimuddin; Akkas, Erwin (JURNAL ATOMIK, 2017)
Research about decreasing of BOD and TSS from waste in ketchup industry with Electrocoagulation method using Fe, Cu and Stainless electrode for decreasing BOD and TSS have been done. Time optimization based by color transformation from Electrocoagulation process have been done. The result of this research from the effect of time contact on Electrocoagulation process are showed the optimized time are 120 minutes whereas the transformation color into transparent color in 12 Volt using Fe-Cu electrode to the decreasing of BOD and TSS are 1800,6 mg/L ; 190 mg/L with the result of percent of elimination are 38,45% ; 68,85% whereas the value of starter of BOD and TSS are 2925,4 mg/L ; 190 mg/L.